Desenvolvimento de algoritmo computacional para dimensionamento e seleção de trocador de calor do tipo casco e tubo - Pires, José Henrique Brandão (2023)
Formally heat exchangers are devices responsible for the transfer of thermal energy between two or more fluids at different temperatures, devices essential for engineers and the industry in general. The design of a shell and tube heat exchanger goes through several levels of complexity, and the method developed by Kern (1983) can be used for dimensional selection of the proposed heat exchanger. The overall goal is to automate the sizing and selection calculations of shell and tube heat exchangers through a fully free computational algorithm developed in the Visual Basic for Applications language, with an interactive window where the user must enter inputs for the sizing calculations. The application has achieved all project objectives, offering an intuitive interface, and speed in the exchanger selection process, through the direct inclusion of data in the code, simplifying the sizing process.